MECHANISM OF REDOX REACTION ON POLYPYRROLE - KIM, DY; CHO, HN; KIM, CY (TECHNOMIC PUBL CO INC, 1994)
A concentration of bipolarons in doped polypyrrole (PPy) decreases on electrochemical reduction at an early stage while that of polarons increases. Further reduction increases the absorption intensity at 800 nm on expense of the peak intensity at 550 nm. Prolonged reduction produces a strong absorption at 400 nm and diminishes the intensities both at 550 nm and 800 nm. The trend of changes in absorption intensity at 800 nm repeats when the reduction system is fixed to pH = 3 by adding acetic acid. However, adding 0.01 mol of hydroquinone in the system lowers monotonically the absorption intensity at 800 nm on reduction. Cyclic voltammograms of the PPy change little after 7,000 cycles if hydroquinone is added to the system. Polarons are so reactive that PPy transforms into irreversible changes in the structure on the reduction process and the reactivity is retarded by adding hydroquinone in the system.